Teachers' use, self-efficacy, and attitude toward the internet - Simon, Audrey B. (2008)
The study examined the relationship between and among teachers' personal characteristics, use, self-efficacy, and attitude towards the Internet. The results of the study became the bases for designing the proposed Internet training program for teachers using the Instructional Systems Design Model by Kemp, Morris and Ross (1994). The study used descriptive method of research. The 124 participants were the in-service teachers form the four clusters of the Isabela State University. Findings indicate that age, number of years in teaching, computer literacy level, and trainings in computer or Internet were all significantly related to teachers' use and attitude towards the Internet. The researcher recommends that there should be more in-service trainings with follow-up that focus on the Internet integration to instruction.